2018
DOI: 10.1017/s1759078718000983
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of patch compensated wideband Vivaldi antenna

Abstract: Design and fabrication of a microstrip feedline-based Vivaldi antenna in the frequency range of 6.0–8.0 GHz have been presented. The Vivaldi antenna is a planar antenna, fabricated at the microstrip feedline by having an exponentially tapered slot profile on it. An optimized computer-aided design has been developed and simulated for the desired radiation parameters like voltage standing wave ratio, bandwidth, directionality, beam-width, etc. The optimized design has been fabricated and tested. Wherever the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A comparison of the proposed Vivaldi antenna with the previously reported Vivaldi antennas in [8][9][10][11][12][13] is tabulated in Table 2. It is revealed, that the proposed antenna is compact and has the highest percentage bandwidth of 164%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of the proposed Vivaldi antenna with the previously reported Vivaldi antennas in [8][9][10][11][12][13] is tabulated in Table 2. It is revealed, that the proposed antenna is compact and has the highest percentage bandwidth of 164%.…”
Section: Resultsmentioning
confidence: 99%
“…In [12], it is shown that elliptical corrugations on the outer edge of AVA with optimal shaping of the inner edges of the antenna result in good impedance matching. Moreover, a patch compensated wideband Vivaldi antenna is reported in [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation